The study of how relationship attribute affect bank customer's saving behaviour: case study in Ipoh, Perak / Aufal Fazan Aziz - Aziz, Aufal Fazan (Faculty of Business and Management, 2019)
Saving is an important part of consumer financial decision making. Compared with other products, saving products are often regarded as more complex and difficult to evaluate due to their sophistication, uncertainty and long-term horizon. Therefore, many consumers decide on saving after consultation with a financial advisor. The purpose of this research is to determine the relationship of how duration of the relationship, the bank advisor's understanding of the customer's context and the customer's trust in the advisor are subjectively perceived by bank customers, and how these affect their saving behaviour, as defined by monthly flows to mutual funds and the financial products bought and held in stock. The researchers identify issues pertaining to effects of financial advisory service on saver's portfolio outcomes. Some research shown that financial advisors have not been able to improve savers' risk weighted return net of fees and instead of de-biasing savers' portfolio, financial advisors have reinforced biases. The research show that larger funds and many banking's activities occurred after meeting of financial advisory services. While this research finds larger volumes of savings after the use of financial advice, there is also a growing body of behavioural science research that deepens knowledge on how the relationship evolves that stimulates the saving volumes and reinforces saving behaviour.